Analisis Kualitas Sensori Ikan Asap Berbahan Bakar Briket Campuran (Arang Bonggol Jagung dan Daun Jati) dan Bahan Bakar Kayu - Dwi Sukowati; Dwi Yanuar Budi Prasetyo; Triat Adi Yuwono (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
This study aims to analyze the sensory quality of smoked fish using mixed briquette fuel (teak leaves and corncob charcoal) with 5% and 10% adhesives with smoked fish using wood fuel. The wood used for comparison is ruby (soft texture) and mahogany (hard texture). Sensory analysis in this study emphasizes the appearances, colors, smells, tastes and textures of smoked fish. To determine whether there is a significant difference or not of the four treatments on the results of smoking fish,this study use Analysis of Varians (Anova). The results showed that there were significant differences between the four methods of feeding fish using briquette and wood fuel on appearances, colors, smells and textures. The appearance, color and aroma that dominate the specifications of other smoked fish are smoked fish with 10% adhesive briquette fuel treatment. The texture of smoked fish with mahogany wood fuel shows better specifications than asp fish with other treatments. Because there is a significant difference, a further test is carried out using BNJ Test. BNJ Test must be done to find out the distinguishing relationship between samples.ÃÂ Whereas in the taste test, there was no significant difference from the treatments